ANTIMYCOBACTERIAL, ANTIOXIDANT AND CYTOTOXIC ACTIVITIES OF ESSENTIAL OIL OF GALL OF PISTACIA ATLANTICA DESF. FROM ALGERIA - Ibrahim, Sifi; Dzoyem, J P; Mohamed, Ouinten; Mohamed, Yousfi; Lyndy, McGaw J.; Jacobus, Eloff N. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: The aim of this study was to assess the antimycobacterial, antioxidant and the cytotoxic activities of the essential oil from the gall part of Pistacia atlantica Desf from Algeria. Materials and Methods: The antimycobacterial activity was evaluated by the broth microdilution method against three species of mycobacteria: Mycobacterium smegmatis, Mycobacterium aurum and Mycobacterium fortuitum. Antioxidant activity was determined using free-radical scavenging assays. The safety of essential oil was assessed by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay on C3A and Vero monkey kidney cells. Results: The minimal inhibitory concentration (MIC) values ranged from 0.16 to 2.5 mg/mL with minimal bactericidal concentration (MBC) values ranged from 0.62 to >2.5 mg/mL. The antioxidant activity showed IC50 values ranged between 417.61 - >2000µg/mL and 495.6 - >2000µg/mL for DPPH and ABTS assay respectively. The cytotoxicity assay showed LC50 ranged between 26.47 to 93.64 µg/mL against Vero cells and 74.29 to 225.40 µg/mL against C3A. The results of this study show that the essential oils from the gall of P. atlantica have low toxicity and moderate activity against fast growing M. smegmatis and M. aurum. Conclusion: These results substantiate their potential as used in the treatment of non-tuberculous mycobacterial infections. This finding is predictive of their activity against M. tuberculosis, therefore, further study might be considered to investigate the activity against pathogenic Mycobacterium strains.